Local Delivery of the Poly-ADP-Ribose-Polymerase-Inhibitor Olaparib From a Biodegradable Paste Potentiates Radiotherapy and Prolongs Survival. (1st September 2019) - Serra, Riccardo; Smith, Stuart J; Rowlinson, Jonathan; Gorelick, Noah L; Veal, Gareth J; Shakesheff, Kevin; Grundy, Richard; Brem, Henry; Rahman, Ruman; Tyler, Betty
Abstract: INTRODUCTION: Olaparib (Lynparza), a PARP (poly-ADP-ribose-polymerase) inhibitor tested in combination with radiation (XRT) and temozolomide, has shown promising results in a recent clinical trial in newly diagnosed Glioblastoma (GBM). To minimize systemic toxicities and increase local drug concentrations, we assessed local delivery of Olaparib from our previously developed PLGA/PEG thermo-sensitive biodegradable paste in an intracranial model of GBM. METHODS: Proliferation, clonogenic, and cell viability were assessed on 9L, U251, and U87 lines to evaluate the efficacy of Olaparib alone and in combination with XRT. Western blotting, immunofluorescence, and flow cytometry with AnnexinV/PI were performed to characterize the pro-apoptotic and radiosensitizing effect of PARP inhibition, along with mRNA-sequencing on 5-ALA positive and negative patient-derived GBM-lines. An in vivo efficacy study was performed on F344 rats implanted with intracranial 9L xenografts (n = 77), and immunohistochemistry analysis carried out on brain samples. RESULTS: Olaparib showed substantial antiproliferative, clonogenic, and cytotoxic activity against all tested lines, and extensive cell apoptosis was demonstrated by means of AnnexinV/PI staining. Western blotting for Apoptosis-Inducing Factor, cleaved-PARP and H2AX, a DNA damage marker, shed light on the molecular targets of Olaparib, and higher mRNA expression of PARP in 5-ALA positive GBM margins provided evidence for effective translatability to human patients. Furthermore, Olaparib/XRT, alone and in combination with temozolomide or etoposide, showed a statistically significant improvement in median (not reached in combination therapy) and overall survival when compared to controls and standard therapy. Combination therapies also achieved long-term survival at rates >50% of the treated cohort. CONCLUSION: Novel treatments for GBM are strongly needed to improve patient survival and quality of life. Interstitial chemotherapy was proven to be a safe and effective approach to increase tumor killing and minimize toxicities. In this study, an intracavitary combination of Olaparib/XRT showed a promising increase in survival, paving the way for future translation to clinical application.